2001
DOI: 10.1098/rspb.2001.1711
|View full text |Cite
|
Sign up to set email alerts
|

The small world inside large metabolic networks

Abstract: The metabolic network of the catabolic, energy and biosynthetic metabolism of Escherichia coli is a paradigmatic case for the large genetic and metabolic networks that functional genomics e¡orts are beginning to elucidate. To analyse the structure of previously unknown networks involving hundreds or thousands of components by simple visual inspection is impossible, and quantitative approaches are needed to analyse them. We have undertaken a graph theoretical analysis of the E. coli metabolic network and ¢nd th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
694
5
2

Year Published

2002
2002
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 861 publications
(722 citation statements)
references
References 44 publications
21
694
5
2
Order By: Relevance
“…Food webs are described as "scale-free" networks (18). In mapping the metabolic network in E. coli, somewhat surprisingly, a scale-free network was identified (19). Subsequently, it was found that the cell's proteome exhibits a similar scale-free topology (20).…”
Section: The Cell's Networkmentioning
confidence: 99%
See 4 more Smart Citations
“…Food webs are described as "scale-free" networks (18). In mapping the metabolic network in E. coli, somewhat surprisingly, a scale-free network was identified (19). Subsequently, it was found that the cell's proteome exhibits a similar scale-free topology (20).…”
Section: The Cell's Networkmentioning
confidence: 99%
“…Three properties are of particular interest. One statistic is the network's characteristic path length, which is the shortest path length measured as the least number of links between two nodes averaged for all pairs of nodes in the network (19,24,26,30). This is a global measure of a network (24,26,30).…”
Section: Scale-free Networkmentioning
confidence: 99%
See 3 more Smart Citations